ZnFe2O4/TiO2 nanocomposite films for photocathodic protection of 304 stainless steel under visible light. (November 2017) - Lei, Jing; Shao, Qian; Wang, Xiutong; Wei, Qinyi; Yang, Lihui; Li, Hong; Huang, Yanliang; Hou, Baorong
Graphical abstract: Highlights: Hydrothermal method for synthesizing ZnFe2 O4 nanoparticles on TiO2 NTs. The photoelectrochemical property of TiO2 could greatly improve by doping ZnFe2 O4 . The ZnFe2 O4 /TiO2 composite films provide a better photocathodic protection for 304SS. Abstract: ZnFe2 O4 sensitized TiO2 nanotubes were fabricated via anodic oxidation and hydrothermal method. The ZnFe2 O4 /TiO2 composite films with different concentrations were synthesized to explore the optimal photoelectrochemical property compared with pure TiO2 nanotubes. The morphology and chemical composition of samples were characterized by scanning electron microscopy, energy-dispersive spectrometry, and X-ray diffraction. The performance of protection for 304 stainless steel was investigated by electrochemical tests, such as open circuit potential and photocurrent density. The results indicate that ZnFe2 O4 /TiO2 composite films showed efficient photocathodic protection effect for 304 stainless steel under visible light, and the optimal specimen composite films shifted the corrosion potential of 304 stainless steel to −780 mV.